Analisi Pengaruh Kualitas Website PT Badak LNG Terhadap Kepuasan Pengguna Menggunakan Metode Webqual 4.0 - Uyun Ilham Zamani; Dewiyani Sunarto; Ignatius Andrian Mastan (Jurnal Sistem Informasi Universitas Dinamika, 2016)
In technological progress, information technology needed a company to support the company performance , no exception the website. Pt Badak NGL is the first company formed to be one of a network in the center by the chain business lng . Now , PT. Badak LNG having a website www.badaklng.co.id .So far , after services website PT. Badak LNG mplemented has never done judgment on its quality perceived the ultimate user or visitors website , so that management website could not receive feedback on the website .There was going to an evaluation of the quality of website PT. Badak LNG . The purpose of this research is to analyze the quality of the website satisfaction users. Hal-hal done in this research among others , makes and spreading the questionnaire to respondents of 86 sample .The results will be processed on the ibm spss version 20 .While the analysis of data in relation done include the validation and reabilitas , the assumption , the test regression together and partial . The Results of research quality website on PT. Badak LNG indicates that dimensions of webqual is variable te usability quality, information quality, and iteraction quality to having influence a positive and significant impact on satisfaction users at the website PT. Badak LNG.